2012
DOI: 10.1097/opx.0b013e31825da430
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Viewing and Reported Perceived Immersion and Symptoms

Abstract: Stereoscopic 3D viewing provides greater immersion, but it can also lead to heightened visual and motion sickness symptoms. Viewers with prior symptoms in viewing TV and computer screen are not more likely to have increased ocular and physical symptoms in 3D viewing. Young viewers incurred higher immersion but also greater visual and motion sickness symptoms in 3D viewing; both will be reduced if a farther distance and a wider viewing angle are adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 25 publications
3
49
1
Order By: Relevance
“…However, we did not find evidence supporting the results from earlier studies that viewing 3D causes more VIMS compared to viewing 2D [2,[24][25][26][27]. Both the SSQ total scores and MISC rates failed to increase substantially more in the 3D session than scores obtained in the 2D session.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, we did not find evidence supporting the results from earlier studies that viewing 3D causes more VIMS compared to viewing 2D [2,[24][25][26][27]. Both the SSQ total scores and MISC rates failed to increase substantially more in the 3D session than scores obtained in the 2D session.…”
Section: Discussioncontrasting
confidence: 99%
“…Confirming previous reports, this study showed that exposure to 2D and 3D motion stimuli can elicit VIMS symptoms [2,4,12,25,26,34,35], as assessed using the SSQ (for both 2D and 3D). However, we did not find evidence supporting the results from earlier studies that viewing 3D causes more VIMS compared to viewing 2D [2,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A substantial amount of research supports the idea that mitigating the vergence-accommodation conflict in stereoscopic displays improves both perception and comfort, and this observation has been a major motivation for the development of displays that support multiple focus distances (3,5,7,(12)(13)(14)(15)27). However, the fact that accommodative gain universally deteriorates with age suggests that the effects of the vergence-accommodation conflict may differ for people of different ages (28)(29)(30) and even that multifocus or dynamic display modes may be undesirable for older users. Because presbyopes do not accommodate to a wide range of distances, these individuals essentially always have this conflict in their day to day lives.…”
Section: Resultsmentioning
confidence: 99%